Pulmonary function, white blood corpuscles & haemoglobin levels in asymptomatic light smokers and non-smokers - Sharath Rao; Purushothaman Pavithran; Shirahatti Krishna Das (International Journal of Medical Research and Review, 2017)
Context: Smoking, a risk factor for several diseases has also been reported as the largest preventable cause of morbidity and mortality globally. Tobacco smoking is associated with a decrease in lung function in smokers when compared to non-smokers.Aims: To study and compare pulmonary function, WBC count and Hb levels in asymptomatic light smokers and non-smokers.Settings and Design: Case control study.Methods and Material: Patient relatives or subjects who had come for health check with a known history of smoking and apparently asymptomatic were recruited as our study subjects (n = 49). Healthy volunteers were also recruited from patient relatives. Subjects without any known history of smoking were selected as controls (n = 50).Statistical analysis used: Data was analysed using SPSS V-19. P value ≤0.05 was considered significant.Results: A statistically significant difference was found in total leucocyte count in smokers (P = 0.004) when compared to non-smokers. There was also a statistically significant increase in absolute neutrophil (P = 0.021), monocyte (P = 0.004) and eosinophil (P = 0.075) counts in smokers. FEV1/FVC (P = 0.005) and FEF 75 (P = 0.027) was significantly higher in non-smokers when compared to smokers. No significant difference was observed in haemoglobin concentration and differential leucocyte count, pulse rate, systolic pressure, diastolic pressure and rate pressure product among the two groups.Conclusions: The present study gives ample evidence for the damage to the respiratory system along with activation of immune system as evident from a significant lowering of small airway patency and increased white cell counts